2021
DOI: 10.3389/fphys.2021.707757
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress and Feed Restriction Distinctly Affect Performance, Carcass and Meat Yield, Intestinal Integrity, and Inflammatory (Chemo)Cytokines in Broiler Chickens

Abstract: This study was conducted to distinguish the effects of heat stress (HS) and feed intake (FI) on broiler chicken’s physiological responses. Day-old male Cobb 500 broilers (n = 672) were allocated to three treatments: (1) control (CTL): birds raised under normal temperature (23°C) from day 29 to 42; (2) cyclic heat stress (CHS): birds exposed to high temperatures (8 h/day at 35°C; from 9:30 am to 5:30 pm) from day 29 to 42; (3) pair-fed (PF): birds raised under thermoneutral condition but fed the same amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…In the study of Emami et al [ 9 ], broilers were exposed to 35 ± 1 °C for 8 h during the age of 29 to 42 days, while the control broilers were kept at 23 °C. Shao et al [ 36 ] applied a similar thermal condition to that used in the study of Emami et al [ 9 ] and reported significant decreases in body weight gain and feed intake in Chinese yellow-feather broilers exposed to the challenge. Souza et al [ 5 ] showed that nutrient utilization and energy metabolism of broilers were not affected by a cyclic thermal exposure (32 °C, 8 h daily).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the study of Emami et al [ 9 ], broilers were exposed to 35 ± 1 °C for 8 h during the age of 29 to 42 days, while the control broilers were kept at 23 °C. Shao et al [ 36 ] applied a similar thermal condition to that used in the study of Emami et al [ 9 ] and reported significant decreases in body weight gain and feed intake in Chinese yellow-feather broilers exposed to the challenge. Souza et al [ 5 ] showed that nutrient utilization and energy metabolism of broilers were not affected by a cyclic thermal exposure (32 °C, 8 h daily).…”
Section: Discussionmentioning
confidence: 99%
“…Duangjinda et al [33] compared the growth performance of broilers and Thai NT chickens under either thermoneutral (26 • C) or chronic thermal stress (36 to 38 • C, 6 h daily) for three weeks and reported the thermal-induced suppression of growth performance for BR but not in the NT chickens. In the study of Emami et al [9], broilers were exposed to 35 ± 1 • C for 8 h during the age of 29 to 42 days, while the control broilers were kept at 23 • C. Shao et al [36] applied a similar thermal condition to that used in the study of Emami et al [9] and reported significant decreases in body weight gain and feed intake in Chinese yellow-feather broilers exposed to the challenge. Souza et al [5] showed that nutrient utilization and energy metabolism of broilers were not affected by a cyclic thermal exposure (32 • C, 8 h daily).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many studies that have revealed the effect of heat stress on broiler growth performance, including mass gain, feed intake, and feed conversion ratio (He et al, 2020;Emami et al, 2021). Broilers are highly heat stress-sensitive (Nassar and Elsherif, 2018) and lose their immune system function, which leads to death (Hirakawa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%